Political Education in Scotland: A Practitioner’s Perspective (Concept: The Journal of Contemporary Community Education Practice Theory, 2016)
By way of introduction, in the build up to the Referendum on Scottish Independence in 2014, I was involved in different bits and pieces of political education work with young people; looking at the issues that were important or personal to them (politics with a small p) and how that connected to governments, policies and decision making (politics with a capital P). For example, a group of young people with specific learning difficulties made connections between issues like bullying, prejudice and discrimination and whether or not there would be greater equality of opportunity if Scotland ruled its own affairs.